ANALYSIS OF LOCAL WISDOM IN AGRICULTURE AND PLANTATION IN TARANTANG VILLAGE, PADANG CITY - Tania Mutiara Rizki (SEMESTA: Journal of Science Education and Teaching, 2021)
Observations were made in Tarantang sub-district Lubuk sub-district of Padang city to find out local wisdom and relate it to science. The purpose of this observation is to prove that the local wisdom of farming that has existed since the days of the ancients is related to the science and science that are developing at this time. The observation activity that we do uses the interview method. The interview was conducted by being recorded. Data obtained is based on local wisdom used by respondents. From the results of the interview it was found that the respondent did not have special education to start farming. Some of the crops from farming are sold to agents, and some are consumed by families.